2022
DOI: 10.1155/2022/8802222
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Mechanical Behaviour of Kevlar and Ramie Fibre Reinforced Epoxy Composites

Abstract: Natural fibre composites have been replacing synthetic fibre composites in practical applications for the last several years because of the features such as low densities, low weight, relatively inexpensive, recyclability, and excellent mechanical qualities unique to the substance. Thus, the current study examines how Kevlar/Ramie/Nano SiC hybrid fibre reinforced composites are made and their mechanical properties, and it compares them to those made using a single natural fibre reinforced composite. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…control the amount of material used and the compression force applied during the moulding process [11]. The resin was mixed with hardener in the ratio of 10:1 [8] and then the reinforcement was added.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…control the amount of material used and the compression force applied during the moulding process [11]. The resin was mixed with hardener in the ratio of 10:1 [8] and then the reinforcement was added.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It was also found additionally that, the sample with 30 wt.% filler showed the greatest moisture diffusivity and mass transfer. Vedanarayanan et al [11] investigated the effect of kevlar and ramie fibre reinforced composites. The results showed that the improvement of tensile and flexural strength up to 30 % weight fraction fiber loading.…”
Section: Introductionmentioning
confidence: 99%
“…Raci Aydin et al [16] investigated the effect of dynamic mechanical analysis of carbon-glass hybrid laminates in different ply angles and found that 12 layered 0 • /90 • angle piles were best suited for natural frequencies, while 30 • /60 • laminates were best suited for damping. Vedanarayanan et al [17] investigated the mechanical properties of Kevlar and ramie fiber composites and found that interlaminar shear strength, tensile, and flexural strength increased by 30%. Yadav et al [18] investigated the effect of nano SiO 2 on the mechanical properties of Kevlar composites and found an increase in hardness and flexural properties by 29% and 50% for 3 wt.% of composites.…”
Section: Introductionmentioning
confidence: 99%